Simultaneous Assessment of Pharmacokinetics of Pilsicainide Transdermal Patch and Its Electropharmacological Effects on Atria of Chronic Atrioventricular Block Dogs - Hiroshi Iwasaki; Akira Takahara; Yuji Nakamura; Yoshioki Satoh; Takeshi Nagai; Norihiro Shinkai; Atsushi Sugiyama (Elsevier, 2009)
Abstract.: Pharmacokinetics of pilsicainide transdermal patch and its electropharmacological effects were simultaneously assessed using chronic atrioventricular block dogs. After application of the patch (9.8 mg/kg), pilsicainide was continuously absorbed through the skin with a Cmax of 0.49 ± 0.13 µg/ml, while its plasma concentration was kept above the clinically reported minimum effective plasma concentration for 2-8h. Inter-atrial conduction time was significantly prolonged, whereas statistically significant prolongation was not detected in the atrial effective refractory period. Prolongation of the cycle length of atrial fibrillation and antifibrillatory action were confirmed. Thus, pilsicainide can be absorbed transdermally to exert long-lasting electropharmacological effects leading to anti-atrial fibrillatory action. Keywords:: pilsicainide, transdermal delivery, atrial fibrillation